Rheumatic heart disease knowledge and associated factors among nurses working in cardiac centers at public and private hospitals of Addis Ababa: cross sectional study - Tesfaye Techane; Bethlehem Legesse; Yohannes Ayalew; Aklil Hailu (BMC, 2022)
Abstract Background It is proposed that the biggest gap in control of rheumatic heart disease is in implementing of ineffective primary and secondary preventive measures. These measures are supposed to be well addressed by nurses. For prevention and proper management, nurses are expected to have full knowledge about rheumatic heart disease. Therefor the main objective of the study was to assess the level of nurse's knowledge and factors behind regarding RHD in the current study. Method Institution based cross sectional study was conducted on nurses working in cardiac centers of public and private hospitals at Addis Ababa from April 1 to 30, 2021. Total sample size is 163 selected by purposive sampling method. Data was entered in to Epi-data version 4.5 and exported to SPSS version 25.0 and was checked for missing values. Data was cleaned. Descriptive statistics such as frequency, mean and percentages were calculated, described and displayed in tables, graphs and charts. Binary logistic regression was done to see the crude significant relation of each independent variable with nurse's good knowledge score. Significant factors were identified based on multivariate logistics regression in 95% confidence level at P-value less than 0.05. Result In the present study about 154 participants were participated. The mean correct answer response of the nurses for knowledge of RHD questions is 12.2 ± 5.2. Only 48.7% of the nurses have good knowledge towards RHD. Being male in gender, having history of sore throat, taking formal education in university or collage, taking in-service training on RHD, having higher wok experience, have found significantly associated with higher odds of nurses' good knowledge towards RHD. Conclusion and recommendation Regular training regarding RHD management should be given to nurses who are working in cardiac centers. Rheumatic heart disease early treatment and prevention should be incorporated and reinforced in to nursing and other health related professions curriculums.